2000
DOI: 10.1191/096120300678828145
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble Fas correlate with indices of organ damage in systemic lupus erythematosus

Abstract: sFas is elevated in sera of SLE patient. Since sFas correlates with indices of organ damage but not with disease activity, it may be a marker of organ damage in SLE and may act to protect certain organs from further damage by inhibiting Fas-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
4
28
0
2
Order By: Relevance
“…We extended these findings by demonstrating in children an association between sFas and sFasL with sepsis-induced liver failure and with SMOF, a liver failure-dependent categorization. FasL on infiltrating lymphocytes may also interact with hepatocyte Fas independent of the effect of circulating sFasL (25,34). Our autopsy results support a role for Fas in sepsisinduced liver injury, possibly mediated by hepatocyte lymphocyte infiltration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We extended these findings by demonstrating in children an association between sFas and sFasL with sepsis-induced liver failure and with SMOF, a liver failure-dependent categorization. FasL on infiltrating lymphocytes may also interact with hepatocyte Fas independent of the effect of circulating sFasL (25,34). Our autopsy results support a role for Fas in sepsisinduced liver injury, possibly mediated by hepatocyte lymphocyte infiltration.…”
Section: Discussionsupporting
confidence: 72%
“…This finding suggests that sFasL may have a different role compared with sFas in the children with severe septic shock. In agreement with adult studies, both sFasL and sFas levels were associated with liver failure and DIC (22)(23)(24)(25)(26)(33)(34)(35). Current literature suggests that sFasL may interact with hepatic Fas and induce liver injury, thereby inducing shedding of sFas (24,25,36).…”
Section: Discussionsupporting
confidence: 68%
“…23 The enhanced serum levels of soluble Fas demonstrated that the intriguing effect of the Fas/FasL pathway on cell death was related to disease activity. [24][25][26] These findings indicate that in SLE patients, the Fas/ FasL pathway plays an important role in immune homeostasis and maintenance of self-tolerance. However, gene mutation in the coding regions of FasL rarely occurs in human lupus patients.…”
Section: Introductionmentioning
confidence: 87%
“…27 The levels of the soluble form of the Fas apoptosis antigen (sFas) were significantly higher in SLE patients than in healthy controls, and sFas levels correlated with organ damage, including ovary damage. 28 Regular menstrual periods are an easily ascertainable external parameter of intact ovarian function; however, the presence of regular bleeding is not synonymous with nonimpaired ovarian reserve. Lawrenz et al 29 found that in premenopausal SLE patients not receiving alkylating therapy, the AMH values were significantly lower compared to the control group.…”
Section: Figmentioning
confidence: 99%